A New Design for Switched-Mode Dental Iontophoresis System Using a Dual-Return Probe - Serkan Dişlitaş (Applied Sciences)
In practice, continuous and pulse direct current (DC) methods are embodied in classical dental iontophoresis systems (CDISs) for the treatment of dentin hypersensitivity (DH). Changes in body electrical resistance and polarization occurrence are the main problems in dental iontophoresis applications. Moreover, continuous DC application may cause discomforts such as irritation, burning and itching on the skin. For these reasons, it is preferred to use pulse DC instead of continuous DC. However, in pulse DC applications, the treatment period is prolonged depending on the decrease in the electrical charge flow. On the other hand, the pain threshold of teeth when the electric current is applied varies from person to person. In this study, in order to reduce the problems caused by the use of CDIS methods for the treatment of DH, a microcontroller-based switched-mode dental iontophoresis system (SMDIS) using a dual-return probe (RP) is designed, and its performance is compared with CDIS methods. According to the results, the new SMDIS both reduces the polarization effect as in the classical pulse DC method and shortens the prolonged treatment duration in pulse DC by raising the pain threshold of teeth due to increased ion transfer, which is a great advantage over former methods.